The new abolition: W.E.B. Du Bois and the black social gospel - Dorrien, Gary J. (Yale University Press, 2015)
"The black social gospel emerged from the trauma of Reconstruction to ask what a "new abolition" would require in American society. It became an important tradition of religious thought and resistance, helping to create an alternative public sphere of excluded voices and providing the intellectual underpinnings of the civil rights movement. This tradition has been egregiously overlooked, despite its immense legacy. In this groundbreaking work, Gary Dorrien describes the early history of the black social gospel from its nineteenth-century founding to its close association in the twentieth century with W.E.B. Du Bois. He offers a new perspective on modern Christianity and the civil rights era by delineating the tradition of social justice theology and activism that led to Martin Luther King Jr."--Publisher's description